2013
DOI: 10.1021/jp311055b
|View full text |Cite
|
Sign up to set email alerts
|

Role of pH, Organic Additive, and Chelating Agent in Gel Synthesis and Fluorescent Properties of Porous Monolithic Alumina

Abstract: This work demonstrates the synthesis of porous monolithic α-alumina by a modified polyacrylamide gel route at different reaction parameters. Various Al2O3 phases are synthesized by a modified polyacrylamide gel route using different organic additives and solutions with different pH values (3, 7, and 11). After calcination at 1150 °C, the pure α-Al2O3 is obtained at pH = 3 and 7 while there is still θ-Al2O3 at pH = 11. The organic additive has nothing to do with the purity of α-Al2O3 phase. The scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The peaks at the binding energy of around 74.1 eV are ascribed to Al 3+ in aluminum oxide. 44,45 The binding energy of around 73.2 eV for other peaks is lower than those of aluminum oxide, which are derived from the strong interaction between Al and Mn owing to an effect of electronic transfer. 46 It also demonstrated that both Al substituted α-MnO 2 and amorphous aluminum oxide exist in the material, in accordance with the XRD and FTIR results (Figure 1b,f).…”
Section: Surface Chemical Statusmentioning
confidence: 98%
“…The peaks at the binding energy of around 74.1 eV are ascribed to Al 3+ in aluminum oxide. 44,45 The binding energy of around 73.2 eV for other peaks is lower than those of aluminum oxide, which are derived from the strong interaction between Al and Mn owing to an effect of electronic transfer. 46 It also demonstrated that both Al substituted α-MnO 2 and amorphous aluminum oxide exist in the material, in accordance with the XRD and FTIR results (Figure 1b,f).…”
Section: Surface Chemical Statusmentioning
confidence: 98%
“…The difference in particle size between samples S1 and S2 reveals that longer calcination times can lead to the growth of LuFeO 3 particles into larger size. Since samples S2-S4 were prepared at the same calcination temperature and time, it is believed that the chelating agent is the key parameter resulting in the particle size/morphology difference between the samples [11]. However, the detailed influencing mechanism of the chelating agent on the size and morphology of LuFeO 3 particles is rather complicated.…”
Section: • Oh Radical Analysismentioning
confidence: 99%
“…Alumina can be synthesized in several metastable transition phases depending on the preparation method as well as synthesis parameters like stirring times, calcination temperature, precursor, solution pH, the starting material, and also additive materials like organic additive and chelating agents 4 , 19 . A well-known group of alumina like η, χ, ρ, and γ-Al 2 O 3 , which labeled as Al 2 O 3 .n H 2 O (n is a number between 0 and 6), is created at low-temperature by dehydration of boehmite and bayerite at ~ 600 °C.…”
Section: Introductionmentioning
confidence: 99%